Cranioplasty with Subcutaneously Preserved versus Cryopreserved Autologous bone flaps after Decompressive Craniectomy- A Comparative Study of 40 Cases - Khalil, Md Ibrahim; Farazi, Md Mohsin Ali; Haque, Md Fazlul; Sorowar, Moutusi; Sheikh, Md Sayedur Rahman; Nurjahan, Kazi (Bangladesh Journal of Neurosurgery, 2021)
Background: After decompressive craniectomy for acute brain swelling, bone flaps need to be stored in a sterile fashion until cranioplasty. We can preserve autologous bone flap as a freeze-preserved state or within abdominal subcutaneous tissue. The aim of this study is to compare the cryopreservation with subcutaneous abdominal preservation regarding the effectiveness and safety. Methods:This is an interventional study. The clinical data of 40 patients underwent decompressive craniectomy and subsequent cranioplasty with autologous bone flaps in Neurosurgery Department of Shaheed Shiek Abu Naser Specialized Hospital and others private Medical Colleges in Khulna from Jan 2018 –December2019.20 patients under cranioplasty using autologous bone stored in ultra low freezer.. Another 20 patients cranioplasty with bone flap preserved in subcutaneous abdominal pocket. The analysis included the rate of complications, bone resorption, and reoperation to compare between SP group and CP group. Results: The mean age was found 35.10(±13.34) years in subcutaneous preserved group and 39.90(±16.40) years in cryopreservation group with male predominance was observed in both groups.The rate of complications occurred in 4 (20%) in the SP group and3 (15%) in the CP group( P =0.677). The rate of bone resorption in SP group was 5.0% and CP group was15.0% (P=0.292). Reoperation in subcutaneous preservation group was 2(10.0%) and in cryopreservation group was 3(15%). The difference was not statistically significant between two groups (p = 0.633). Conclusion: SP and CP both might be effective and safe methods for the storage of bone flaps for cranioplasty. There were no significant difference in complications, bone resorption , reoperation among two groups. However, identifying of the method that gives better results might depend on the individual surgeons preference and available equipment. Bang. J Neurosurgery 2021; 10(2): 201-205